Extent of Linkage Disequilibrium and Effective Population Size in Four South African Sanga Cattle Breeds - Makina, Sithembile O.; Taylor, Jeremy F.; van Marle-Köster, Este; Muchadeyi, Farai C.; Makgahlela, Mahlako L.; MacNeil, Michael D.; Maiwashe, Azwihangwisi (Frontiers in Genetics, 2015)
Knowledge on the extent of linkage disequilibrium (LD) in livestock populations is essential to determine the minimum distance between markers required for effective coverage when conducting genome-wide association studies. This study evaluated the extent of LD, persistence of allelic phase and effective population size (Ne) for four Sanga cattle breeds in South Africa including the Afrikaner (n=44), Nguni (n=54), Drakensberger (n=47) and Bonsmara breeds (n=46), using Angus (n=31) and Holstein (n=29) as reference populations. We found that moderate LD extends up to inter-marker distances of 40-60 kb in Angus (0.21) and Holstein (0.21) and up to 100 kb in Afrikaner (0.20). This suggests that genomic selection and association studies performed within these breeds using an average inter-marker r2 ≥ 0.20 would require about 30,000 -50,000 SNPs. However, r2 ≥ 0.20 extended only up to 10-20 kb in the Nguni and Drakensberger and 20-40 kb in the Bonsmara indicating that 75,000 to 150,000 SNPs would be necessary for genome-wide association studies in these breeds. Correlation between alleles at contiguous loci indicated that phase was not strongly preserved between breeds. This suggests the need for breed-specific reference populations in which a much greater density of markers should be scored to identify breed specific haplotypes which may then be imputed into multi-breed commercial populations. Analysis of effective population size based on the extent of LD, revealed Ne=95 (Nguni), Ne=87 (Drakensberger), Ne=77 (Bonsmara) and Ne=41 (Afrikaner). Results of this study form the basis for implementation of genomic selection programs in the Sanga breeds of South Africa.